Efficacy of Plaque Control by Tooth Brushing with and without Different Dentifrices: A Clinical Trial - Yaghini, Jaber; Naghsh, Narges; Tavakoli, Mohammad; Ghoreishi, Saeedeh; Azari, Alireza; Mogharehabed, Ahmad; Kiyani, Sima (Journal of Dental School, 2019)
Objective: Microbial plaque is among the main etiologies of periodontal disease, and tooth brushing with toothpaste is the most commonly used method of plaque control. This study aimed to compare the efficacy of tooth brushing with and without three different dentifrices. Methods: Thirty dental students were randomly selected to participate in this clinical trial and were asked to refrain from any plaque control measure for 24 hours. Candidates were then randomly assigned to one of the three groups of tooth brushing with Pooneh whitening toothpaste, Crest 3D White, Sensodyne Original and tooth brushing without toothpaste. Subjects were asked to brush their teeth for two minutes using the Bass technique. Plaque index was calculated before and after the intervention. This process was repeated until all subjects experienced all the understudy interventional protocols (tooth brushing with three different toothpastes and without toothpaste). Data were analyzed by repeated measures ANOVA and paired t-test. Results: No statistically significant difference was noted in the efficacy of plaque control by tooth brushing with Crest 3D White and Sensodyne Original and tooth brushing without toothpaste; however, significant differences were noted in this respect between Pooneh toothpaste and the remaining three tooth brushing protocols (p≤0.001). Conclusion: Tooth brushing without toothpaste may have a plaque control efficacy equal or even higher than that of tooth brushing with toothpaste.